Origens do presidencialismo no Brasil: um estudo sobre o pensamento político republicano no Segundo Reinado - Vinícius Batelli de Souza Balestra (2021)
This thesis proposes to understand the origins of the presidential system of government in Brazil, investigating the republican ideologies that emerged during the Second Reign. The thesis begins underlining how the Brazilian political elite was concerned with reconciling liberal ideology and conservative pragmatism. This will be the conception of government attacked by republicanism. The political crisis between the Crown and the Liberal Party in 1868 inaugurates a time of calls to the Empire, in which the Republican Party emerged. The republican criticism of the “personal power of the King” receives special attention, as it allows for a contrast with the republican practice itself from 1889 onwards, and its insistence on federalism. Discussions about the abolitionist movement are also addressed, emphasizing the limits and contradictions of the imperial government system. The thesis underlines the alliance between the military and the Republican Party for the November 15 coup and seeks to demonstrate that the main republican groups were united around a political model that combined oligarchical command and draining the powers of parliament. The ideological division between liberal republicans and positivists, regarding the government system, vanishes: Brazilian republicanism, ideologically conservative, defended a centralized and authoritarian model of government, personalized in the President of the Republic.